Contribution of Postjunctional M2 Muscarinic Receptors to Cholinergic Nerve-Mediated Contractions of Murine Airway Smooth Muscle. Issue 1 (20th October 2021) - Alkawadri, Tuleen; McGarvey, Lorcan P; Mullins, N D; Hollywood, Mark A; Thornbury, Keith D; Sergeant, Gerard P
Abstract: Postjunctional M2Rs on airway smooth muscle (ASM) outnumber M3Rs by a ratio of 4:1 in most species, however, it is the M3Rs that are thought to mediate the bronchoconstrictor effects of acetylcholine. In this study, we describe a novel and profound M2R-mediated hypersensitization of M3R-dependent contractions of ASM at low stimulus frequencies.. Contractions induced by 2Hz EFS were augmented by > 2.5-fold when the stimulus interval was reduced from 100 to 10 s. This effect was reversed by the M2R antagonists, methoctramine, and AFDX116, and was absent in M2R null mice. The M3R antagonist 4-DAMP abolished the entire response in both WT and M2R KO mice. The M2R-mediated potentiation of EFS-induced contractions was not observed when the stimulus frequency was increased to 20 Hz. A subthreshold concentration of carbachol enhanced the amplitude of EFS-evoked contractions in WT, but not M2R null mice. These data highlight a significant M2R-mediated potentiation of M3R-dependent contractions of ASM at low frequency stimulation that could be relevant in diseases such as asthma and COPD. Graphical Abstract: